Protection of Human Rights on The Rights of Indigenous Communities In Sesar Village Due To Coastal Reclamation - Tahamata, Lucia; Hattu, Vonda Vidya (Ridwan Institute, 2021)
The right to the environment is a basic right that must be fulfilled by the state because it is a human right, for the community without guarantees. Protection of the right to the environment is the state's obligation in this case the local or district government. This study aims to identify and discuss the protection of human rights for the rights of indigenous peoples due to coastal reclamation and the state's responsibility for the rights of indigenous peoples due to the absence of environmental permits in coastal reclamation activities. This type of juridical empirical research uses a literature review based on theories, doctrines, and legal norms related to the issues discussed. This research is analytical prescriptive by explaining the problems raised based on legal provisions, norms, and theories and then analyzed qualitatively. The results showed that the protection of human rights to indigenous peoples due to the absence of environmental permits would impact the rights of indigenous people,s in this case, the right to survival. Moreover, the land of customary territory has been transferred under companies that exploit natural resources and enrich themselves. This also worsens their right to survival. For that, the active role of the community is also needed when seeing something that is suspicious, which will impact people's rights. For this reason, it is also expected that the community and local governments must build cooperation so that the environment remains managed and utilized, following the principles of development sustainability